Anti-militarism political and gender dynamics of peace movements - Cockburn, Cynthia (Palgrave Macmillan, 2012)
People come together in movements to end war from many political traditions. They are socialists, communists and anarchists, people of a variety of faiths, secularists, pacifists and feminists. They share a belief that peace is possible, but have divergent views on the causes of militarism and strategies to end it. As both peace activist and social researcher, Cynthia Cockburn is well placed to ask, 'How coherent and cohesive are we?' The book presents original case studies of anti-war, anti-militarist and peace movements in Japan, South Korea, Spain, Uganda and the UK, of international networks against military conscription and the proliferation of guns, and of singular campaigns addressing aggression against Palestinians and the expansion of NATO. The stand-alone chapters make ideal course readings. Scanning the political spectrum, but always with a gender lens, the author carefully uncovers the movements' many tensions and antagonisms, looking for the source of alliance that may make of these and a multitude of other groups, organizations and networks worldwide an unstoppable movement for change. Between the nihilist view that violence is inevitable and the utopian belief in the possibility of a violence-free world is an achievable goal of violence reduction, both in times of war and in times called peace. Violence is, much more often than we think, a choice.